Indonesia's Diplomacy in Establishing the Indonesian Language as an Official Language of UNESCO - Laode Muhamad Fathun; Nidatya, Nurfarah; Lumumba, Patrice; Saepudin; Aldebaran Raihan Revidy (Hasanuddin Journal of International Affairs, 2025)
This research aims to explain Indonesia's diplomacy to make Bahasa Indonesia an official language at UNESCO. This research was conducted because Indonesian is one of the languages with the largest number of speakers in the world. In addition, Indonesian is also a form of Indonesia's soft power to the world. This research applied the concept of language as power and diplomacy theory for analysis, utilizing a literature review approach. The results of this study show that Indonesian diplomacy is carried out through shutle diplomacy and total diplomacy, by mobilizing all components of the nation as well as sustainable actions in accordance with the mandate of the Ministry of Education and Culture Regulation. So that all elements of the nation have a duty to do this through various ways. One of them is done through educational channels such as BIPA, or cooperative institutions with governments in various countries to study Indonesia comprehensively. This BIPA phenomenon is the first step to learning about Indonesia holistically. Indonesian diplomacy is also successful because various countries have used Indonesian as part of communication in addition to the official language, for example Vietnam, Canada, Poland, Australia etc.